2022
DOI: 10.1021/acssuschemeng.2c00098
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the Activity-Selectivity Trade-Off of Pt Nanoparticles Encapsulated in UiO-66 for Hydrogenation by Constructing Suitable Hierarchical Structure

Abstract: The simultaneous enhancement of activity and selectivity during hydrogenation is a great challenge. Herein, by encapsulating Pt nanoparticles (NPs) into the hierarchical defective metal−organic framework (MOF) of UiO-66, the steric screening effect of the pores, Lewis acid sites of the nodes, and metal-MOF synergy have been finely tuned and effectively utilized for selective hydrogenation. Benefiting from optimal meso/micropores, favorable Lewis acid sites and strengthened metal−support interaction, Pt NPs enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 63 publications
0
11
0
3
Order By: Relevance
“…Guo et al also reported that the exposed defect sites in MOFs acted as the Lewis acid sites for the adsorption and activation of both C=O groups and H 2 . 116 The Lewis acid sites together with the proper mesopores greatly promoted the adsorption cooperation in boosting the catalytic performance though decoupling the H 2 dissociation sites and hydrogenation sites. The synergy effect between the organic framework and metal sites is very similar to the non-contact hydrogenation mode of reductases.…”
Section: Activation Of Substratementioning
confidence: 99%
See 1 more Smart Citation
“…Guo et al also reported that the exposed defect sites in MOFs acted as the Lewis acid sites for the adsorption and activation of both C=O groups and H 2 . 116 The Lewis acid sites together with the proper mesopores greatly promoted the adsorption cooperation in boosting the catalytic performance though decoupling the H 2 dissociation sites and hydrogenation sites. The synergy effect between the organic framework and metal sites is very similar to the non-contact hydrogenation mode of reductases.…”
Section: Activation Of Substratementioning
confidence: 99%
“…Guo et al also reported that the exposed defect sites in MOFs acted as the Lewis acid sites for the adsorption and activation of both C O groups and H 2 . 116 The Lewis acid sites together with the appropriate mesopores greatly promoted the adsorption and activation of reactants, leading to the breaking of the trade-off relationship between selectivity and activity.…”
Section: Activation Of Substratesmentioning
confidence: 99%
“…Note also that H 2 evolution occurred smoothly without CO generation on most catalysts in the current study, an attractive feature for the practice of the green production of H 2 . 39 As shown in Figure 13, comparisons of the FA conversion rate and H 2 formation rate are made over Pt/r.d-SnO 2 -ALD and Pt/o-SnO 2 -ALD. The FA conversion rate at different S9 are the results of such an investigation conducted on the two representative catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…Among various treatment approaches, the catalytic conversion method can not only reduce the environmental risks in the process of pollutant treatment but also produce the pharmaceutical intermediate aminophenol (AP) products. Among various kinds of catalysts, metal nanoparticles (e.g., aurum NPs, argentum NPs, palladium NPs, platinum NPs, and nickel NPs , ) as a kind of catalyst for nitrophenols reduction has been extensively studied. Compared with other metal nanoparticles, palladium nanoparticles (Pd NPs) have two unique properties: (1) their catalytic activities have a nanometer scale effect; , (2) they are still active even under low temperature, strong acid and/or base conditions .…”
Section: Introductionmentioning
confidence: 99%